Analyzing the Quality of Instrument for Critical Thinking Skill and Assessing Students’ Critical Thinking Skill in Ecology using the Rasch Model - Tantri Taniaa; Sajidan Sajidan; Harlita Harlita (Universitas Sebelas Maret, 2020)
One competency needed to face 21st-century challenges is critical thinking. In assessing students' critical thinking skills, a proper instrument is needed. This study was aimed to analyze the instrument and find out the students' critical thinking skills. The aspects of critical thinking have been detailed by Facione. They were interpretation, analysis, inference, evaluation, explanation, and self-regulation. The test of critical thinking skills was used as an instrument. This was a quantitative descriptive study conducted on 36 tenth-grade students in Surakarta and Pacitan. Data were analyzed by using Rasch Model with Winstep Software. The reliability of the item was 0.86, which means the instrument has good reliability. Also, validity tests showed the instrument was valid. The validity of the instrument was assessed based on the criteria by Boone: MNSQ, ZSTD, and PTMEASUR CORR. All items were valid. The instrument has good reliability. The results showed the students’ critical thinking skills were still low. It is shown from the results of the average logit value of -0.74. The level of difficulty sorted out from the most difficult questions were analysis, evaluation, explanation, self-regulation, interpretation, and inference. Many students cannot give the correct answers to the low difficulty questions as shown by the Wright Map. The results showed that the instrument was valid and reliable and can be used for further research, and there is a need to improve students' critical thinking skills